A Novel Algorithm for Lifetime Extrapolation, Prediction, and Estimation of Emerging PV Technologies. Issue 1 (1st December 2017) - Rizzo, Antonio; Cester, Andrea; Madsen, Morten V.; Krebs, Frederik C.; Gevorgyan, Suren A.
Abstract: Accurate determination of the lifetime of novel hybrid and organic solar cells is often rather challenging due to the very dynamic behavior of such cells over time and ageing curves with shapes of varying nature. Therefore, in order to accurately and reproducibly determine the lifetime of photovoltaic devices with such a behavior, a novel elaboration algorithm is developed, which enables automatic smoothing, filtering, and extrapolation of the real lifetime data and reproducible determination of the lifetime parameters defined in the International Summit on OPV Stability guiding standards. The algorithm is also capable of predicting the lifetime of devices, not tested until the end of sample life, given that there is sufficient number of measured data points to perform reliable extrapolation of ageing curves (to a limited time frame). The algorithm is discussed in detail and a range of examples for different lifetime data are presented. Abstract : Determination of lifetime parameters from ageing curves of novel photovoltaic technologies with very dynamic behavior is rather challenging and a critical issue. An algorithm for extracting the lifetime parameters from ageing curves of any nature in an accurate and reproducible manner is presented. The method allows the lifetime performance of different samples produced in the same or different laboratories to be compared fairly.